Peran underwriter sebagai komunikator pemasaran saham perdana di bursa efek Indonesia - Istikhoroh, Siti; Jannah, Maula Miftahul; Sukamdani, Yuni; Suhardiyah, Martha (Jurnal Studi Komunikasi, 2022)
Companies use Initial returns as a powerful marketing tactic to attract investors to buy IPO shares. This phenomenon is quite popular among investors, but can be detrimental to the issuer/company, so persuasive communication is needed by the Underwriter who is a third party to assist the company in persuading potential investors to get the best value. This study aims to understand the role of the Underwriter as a communicator for the marketing of initial shares on the Indonesia Stock Exchange, whose role is to organise and provide trading facilities. This study involved 49 companies that conducted Initial Public Offerings (IPOs) and were listed on the Indonesian Stock Exchange in 2019. This study places the Underwriter as an external party who is responsible for communicating financial conditions to potential investors for the most reasonable price. Underwriter's role as a communicator is practiced through marketing communications which is a method of delivering targeted information to clients in the fastest and most efficient way possible. The data that has been obtained is then analysed by Moderated Regression Analysis. The results of this study indicate that the Underwriter is able to moderate the relationship with investors during the IPO with the reputation of the Underwriter. This is because the Underwriter is able to persuade investment decisions during the marketing of the IPO.